From Heroism to Lese-Majesty, Circassian Ethem, the Formation and Winding up of Mobile Troops - Kılavuz, Nuran (Fırat University, 2011)
Anatolian nation, which was left Armistice of Mudros, formed Turkish which were local resistance organizations in order to defend itself. Especially the Greek’s occupying İzmir on 15 May 1919 caused locals to be organized quickly. One of the most important of these irregular public organizations was Mobile Troops formed by Circassian Ethem’s leadership. This squad played effective role in getting strong of central authority by showing great effectiveness in defiance to the occupations and counterinsurgency of the local riots. Circassian Ethem and his troops disclaimed the authority after for a while. Eventually, Circassian Ethem, who was in conflict with Ankara Administration especially in the matter of transition to standing army, took refuge in İzmir occupied by the Greeks by not being able to resist the authority. Thus, Circassian Ethem and Circassian Ethemhis brothers were proclaimed as traitors.

Mondros Ateşkes Antlaşmasıyla savunm ılan Anadolu halkı, kendini savunmak için yerel d Anatolian nation, which was left Armistice of Mudros, formed Turkish Revolu obile Troops and its Winding up. of Mobile Troops 1 ÖZET asız bırak ireniş örgütleri olan Kuva-yı Milliye birliklerini oluşturdu. Özellikle 15 Mayıs 1919’da Yunanlıların İzmir’i işgal etmesi, bölge halkının hızlıca teşkilatlanmasına neden oldu. Bu düzensiz halk örgütlenmelerinin içinde en önemlilerinden biri de Çerkez Ethem’in öncülüğünde kurulan Kuvve-i Seyyare’dir. Bu birlik, işgallere karşı koymada ve yerel isyanları bastırmada büyük yararlılık göstererek, merkezi otoritenin güçlenmesinde oldukça etkin rol oynamıştır. Çerkez Ethem ve kuvvetleri, belirli bir dönemden sonra otorite tanımaz hale gelmiştir. Özellikle düzenli orduya geçiş konusunda Ankara Hükümeti ile çatışan Çerkez Ethem, sonunda otoriteye karşı koyamayıp, Yunanlıların işgal ettiği İzmir’e sığınmıştır. Böylelikle Çerkez Ethem ve biraderleri vatan haini ilan edilmiştir.
KAHRAMANLIKTAN VATAN HAİNLİĞİNE, ÇERKEZ ETHEM, KUVVE-İ SEYYARE’NİN TEŞKİLİ VE TASFİYESİ